Familial hypercholesterolaemia: genetic causes and treatment - Humphries, Steve (Henry Stewart Talks, 2023)
Familial Hypercholesterolaemia (FH), FH diagnostic criteria, Gene mutations involved in FH development, LDLR gene, APOB gene, PCSK9 gene, FH treatment, Statins, Homozygous FH